2019
DOI: 10.1007/s42729-019-00098-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved Growth and Nutrition of Sorghum (Sorghum bicolor) Plants in a Low-Fertility Calcareous Soil Treated with Plant Growth–Promoting Rhizobacteria and Fe-EDTA

Abstract: The low availability of micronutrients such as zinc (Zn) and iron (Fe) and macronutrients (phosphorus (P), in particular) in calcareous soils adversely affects plants such as sorghum (Sorghum bicolor) that are highly sensitive to deficiencies of these elements. This study investigated the potential effects of different Fe chelates and plant growth-promoting rhizobacteria (PGPR) on nutrition and growth of sorghum plants growing in a low-fertility calcareous soil. A glasshouse experiment was carried out in a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Furthermore, the production of IAA by PSB-18 (46.14 μg ml −1 ) and RB-1 (30.64 μg ml −1 ) (Jha 2016) has a positive effect on plant growth as they stimulate lateral root proliferation which leads to increase in absorption area and results in more absorption of nutrients from the soil which ultimately leads to more nutrient concentration in plants as compared with the uninoculated control. PGPR increased phosphorus concentration and phosphorus and potassium uptake in sorghum (Abbaszadeh-Dahaji et al 2020), as also observed in the present study.…”
Section: Effect Of Biofertilizerssupporting
confidence: 91%
“…Furthermore, the production of IAA by PSB-18 (46.14 μg ml −1 ) and RB-1 (30.64 μg ml −1 ) (Jha 2016) has a positive effect on plant growth as they stimulate lateral root proliferation which leads to increase in absorption area and results in more absorption of nutrients from the soil which ultimately leads to more nutrient concentration in plants as compared with the uninoculated control. PGPR increased phosphorus concentration and phosphorus and potassium uptake in sorghum (Abbaszadeh-Dahaji et al 2020), as also observed in the present study.…”
Section: Effect Of Biofertilizerssupporting
confidence: 91%
“…The combination of four strains level improved plant ability for nutrients absorption like Mn by expanding the host root system and increasing root contact with soil as a result of more lateral root and root hair production. Abbaszadeh-Dehaji et al 48 reported that three PGPRs (Pseudomonas putida P159, Pseudomonas flurescens T17-24 and Bacillus subtilis P96) inoculation resulted from a significant increase in sorghum growth and nutrients like Mn, Zn, Cu, and K in plant leaf in compare with control plants. Malekzadeh et al 49 showed that Fe, Zn, P and Mn absorption by maize shoot increased significantly in all inoculated treatments with Bacillus mycoides and Micrococcus roseus in compare with control.…”
Section: Discussionmentioning
confidence: 99%
“…Low organic matter content and nutrient availability particularly phosphorus (P) and micronutrients (Fe, Mn, Zn, and Cu) are common problems in calcareous soils in arid zones (Rengel 2015;Abbaszadeh-Dahaji et al 2019;Bityutski et al 2017;Kumari et al 2018). The decrease in soil organic matter negatively affects the soil nutrient availability (Naeem et al 2017) and microbial activity (Khadem and Raiesi 2017a).…”
Section: Introductionmentioning
confidence: 99%